Electronic and surface modulation of 2D MoS2 nanosheets for an enhancement on flexible thermoelectric property. (7th May 2023) - Yang, Yaocheng; He, Dunren; Zhou, Yuan; Wen, Shuangchun; Huang, Huihui
Abstract: Two-dimensional materials have potential applications for flexible thermoelectric materials because of their excellent mechanical and unique electronic transport properties. Here we present a functionalization method by a Lewis acid-base reaction to modulate atomic structure and electronic properties at surface of the MoS2 nanosheets. By AlCl3 solution doping, the lone pair electronics from S atoms would enter into the empty orbitals of Al 3+ ions, which made the Fermi level of the 1T phase MoS2 move towards valence band, achieving a 1.8-fold enhancement of the thermoelectric power factor. Meanwhile, benefiting from the chemical welding effect of Al 3+ ions, the mechanical flexibility of the nanosheets restacking has been improved. We fabricate a wearable thermoelectric wristband based on this improved MoS2 nanosheets and achieved 5 mV voltage output when contacting with human body. We think this method makes most of the transition metal chalcogenides have great potential to harvest human body heat for supplying wearable electronic devices due to their similar molecular structure.